カニクイアザラシ ノ ナイゾウ ノ ケイタイ カンサツ - 西田, 司一; ニシダ, シイチ; 雨宮, 淳三; アメミヤ, ジュンゾウ; NISHIDA, Shiichi; AMEMIYA, Junzo (国立極地研究所, 1962)
P(論文) Some entrails and an embryo of a crab-eating seal captured in Antarctica (69°01'S, 30°41'E) were examined from the standpoint of morphology. This paper describes the characteristics observed with the naked eye. The dissection was performed after the material was melted indoors, as it had been frozen, and the features of entrails, weight, colour, and so on were chiefly examined. The dissected parts were kept in a 10 per-cent formalin liquid and were examined again later. departmental bulletin paper